Voice, trust, and memory marginalized groups and the failings of liberal representation - Williams, Melissa S., 1960- (Princeton University Press, 2000)
A presentation of the argument that fair political representation for disadvantaged groups requires their presence in legislative bodies, which states that this can be done without compromising principles of democratic freedom and equality.